Purse Seine Fleet Optimization with E-Logbook Data in GoronPost-Election Communication Drives Reconciliation in Tallung Ura Villagetalo Fisheries: Komunikasi Pasca Pilkada Mendorong Rekonsiliasi di Desa Tallung Ura - Mutia Husnah; Haidir Fitra Siagian; Anggriani Alamsyah; Arifuddin Arifuddin; Kamaluddin Tajibu (Academia Open, 2026)
General Background: Local elections in Indonesia frequently trigger polarization, damaged social relations, and prolonged distrust within communities. Specific Background: In Tallung Ura Village, Enrekang Regency, the 2024 election created social fragmentation, emotional tension, and disrupted daily interactions among residents. Knowledge Gap: Limited research addresses reconciliation models that apply communication strategies integrating religious values and local cultural wisdom in rural settings. Aims: This study analyzes the roles of communicators, communication mechanisms, and strategies that support post-election reconciliation. Using a qualitative case study, data were obtained through observation, interviews, and documentation with religious leaders, village authorities, and community actors. Results: Reveal that local communicators acted as mediators delivering persuasive, empathetic messages; open dialogue and personal mediation reduced tensions; and strategies grounded in Islamic teachings and cultural values such as sipakatau, sipakalebbi, and sipakainge rebuilt trust and social cohesion. Novelty: Lies in presenting a reconciliatory communication model based on spiritual guidance, cultural identity, and participatory mechanisms unique to Tallung Ura and rarely examined in political reconciliation literature. Implications: Indicate that strengthening mediator capacity and establishing communication forums may provide a transferable framework for restoring grassroots harmony and preventing recurring conflict in similar post-election contexts. Highlights • Mediators used persuasive and empathetic communication to reduce tensions.• Religious principles and cultural values supported sustainable reconciliation.• Structured dialogue forums restored trust and rebuilt social cohesion. KeywordsPost-Election Communication; Reconciliation Strategy; Local Mediators; Cultural Values; Social Cohesion